A descriptive study on the assessment of an academic library's interior design components in relation to universal design guidelines - Avila, Karla C.
ABSTRACT This descriptive study aimed to make an in-depth assessment of the interior design components in an academic library in relation to universal design guidelines. The study documented the interior design components in the chosen academic library, assessed and analyzed their conditions in relation to universal design guidelines, and identified interior design components which can be altered and improved. A qualitative approach was employed in the study with observation and survey as the data collection methods. Twenty (20) library user survey respondents were selected for the study through convenience sampling. The result of the study only showed the assessment for each of the interior design components and not an evaluation of the whole library?s interior design. Generally, the entrance to the library follows universal design guidelines as its clear opening width allows ample space for users to pass by. The flooring surface is also acceptable based on the assessment with a just a few minor vertical level changes identified. Most of the circulation spaces in the academic library have satisfactory widths, but a few circulation spaces do not meet the minimum requirements making them less practical for the users. The fundamental furniture pieces, which include the library chairs, tables, and bookshelves, are satisfactory as reflected in the survey results. For the signage, the general assessment resulted to the signs not being consistent throughout the space. The signs offering selective visibility due to their locations and their lack of presentation style also manifested in the study.